2003
DOI: 10.1177/194589240301700111
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Anatomy of the Sphenopalatine and Posterior Nasal Arteries: Implications for the Endoscopic Management of Epistaxis

Abstract: Understanding this anatomic relationship is important in performing endoscopic arterial ligation. If the sphenopalatine artery is not specifically identified and ligated, an important component of the posterior nasal circulation will not be addressed adequately by this surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 21 publications
7
70
0
4
Order By: Relevance
“…If nasal pack for controlling severe epistaxis leads to pain and extreme discomfort and if nasal obstruction, dysphagia and occlusion of auditory tube are present and no response can be obtained from medication and pack therapy, arterial ligation is applied (Abelson et al; Maceri). Transanthral, transoral or endonasal endoscopic intervention methods are used for ligating the 3rd part of the maxillary artery and sphenopalatine artery (Stepnick et al, 1990;Abelson et al;Maceri;Voegels et al, 2001;Schwartzbauer et al;Kumar et al, 2003;Pradess et al, 2008;Abuzayed et al). Arterial embolization is used as an alternative and efficient method for persistent posterior epistaxis cases and it is performed under angiographic guidance (Maceri).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If nasal pack for controlling severe epistaxis leads to pain and extreme discomfort and if nasal obstruction, dysphagia and occlusion of auditory tube are present and no response can be obtained from medication and pack therapy, arterial ligation is applied (Abelson et al; Maceri). Transanthral, transoral or endonasal endoscopic intervention methods are used for ligating the 3rd part of the maxillary artery and sphenopalatine artery (Stepnick et al, 1990;Abelson et al;Maceri;Voegels et al, 2001;Schwartzbauer et al;Kumar et al, 2003;Pradess et al, 2008;Abuzayed et al). Arterial embolization is used as an alternative and efficient method for persistent posterior epistaxis cases and it is performed under angiographic guidance (Maceri).…”
Section: Discussionmentioning
confidence: 99%
“…Although course and parts of the maxillary artery are defined in classical anatomy books, significant clinical information related with the main artery and its branches are included in several investigation reports (Navarro et al, 1982;Morton & Khan, 1991;Vrionis et al, 1996;Sashi et al, 1996;Choi & Park, 2003;Schwartzbauer et al, 2003;Isolan et al, 2007;Hussain et al, 2008;Abuzayed et al, 2009;Chiu, 2009;Kwak et al, 2010). As the most important contribution to the blood supply of the nose is made by maxillary artery from the external carotid system, it is reported that ligation of the maxillary artery and its branches via different procedures is the most efficient method for controlling the epistaxis (Stepnick et al, 1990;Abelson, 1991;Maceri, 1993;Abuzayed et al, 2009;Kwak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This helped in the stoppage of the bleeding in many cases. There are many other methods that can be applied for the treatment of these cases, like lasers [11,13,14], cryotherapy, endoscopic ligation of the sphenopalatine artery [15], and endoscopic ligation of the ethmoidal arteries [15,16]. As these facilities were not available in our hospital, the above mentioned procedures were not done.…”
mentioning
confidence: 99%
“…[9][10][11] It is important to consider that certain anatomic variations exist in the blood supply of the sphenopalatine artery, one of which is that the posterior lateral nasal artery may extend anteriorly to the posterior wall of the maxillary antrum. 12,13 This variant in particular is important to recognize in avoiding injury to the vascular pedicle when performing the maxillary antrostomy and mucoperiosteal elevation.…”
Section: Surgical Techniquementioning
confidence: 99%